Organoiron-mediated synthesis and redox activity of organoiron-containing dendrimers. (28th January 2015) - Astruc, Didier; Wang, Yanlan; Rapakousiou, Amalia; Diallo, Abdou; Djeda, Rodrigue; Ruiz, Jaime; Ornelas, Catia
Abstract : Graphical abstract: The construction, redox properties and applications of organoiron dendrimers are discussed in this micro-review. Abstract: In this micro-review, the concepts that have led to ligand activation and redox robustness with organoiron complexes in the authors' laboratory are developed. It is shown how these activation modes have led to the construction of redox-active metallodendrimers including various types of mixed-valent complexes with application to redox recognition, sensing and controlled nanoparticle synthesis.